Silicon Quantum Dots Metal-Enhanced Photoluminescence by Gold Nanoparticles in Colloidal Ensembles: Effect of Surface Coating - Romero, Juan José (2018)
In the present study, we report the photophysical properties of colloidal ensembles of silicon quantum dots (SiDs) and gold nanoparticles (AuNPs), particularly focusing on investigating metal-enhanced photoluminescence (PL) effects. AuNPs with different sizes, (27 ± 10) and (88 ± 12) nm, and ca. 3.4 nm-size SiD with different surface groups, either covered with an oxidized surface film bearing Si-OH surface groups or grafted with propylamine leading to Si-(CH2)2-CH2-NH2 terminal functionalities, were tested to evaluate the gold enhancement of SiD PL. The NPs were characterized by high-resolution transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, inductively coupled plasma atomic emission spectroscopy, and gel electrophoresis, whereas the photophysical properties of the NPs, alone and in colloidal ensembles at different concentrations, were investigated by absorption and steady-state and time-resolved PL studies, including quantum yield determinations. Enhanced absorption and PL of SiDs in the presence of AuNPs was evidenced, leading in the most favorable cases to ca. 10 times increase in SiD brightness. This effect depends strongly on the SiD surface coating and its interaction with citrate-capped gold surfaces, where these interactions govern particle aggregation and relative distance distributions among SiDs and AuNPs in the ensembles. The nature of these interactions and how they affect metal-enhanced luminescence is thoroughly discussed. The present study provides significant information on the effect of SiD surface groups and surface charge on the metal-enhanced luminescence phenomenon in colloidal aqueous suspensions.